1998
DOI: 10.1046/j.1469-0705.1998.11060407.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and early childhood follow‐up of chromosomally normal fetuses with increased nuchal translucency at 10–14 weeks' gestation

Abstract: The aim of this study was to evaluate pregnancy outcome and early childhood of chromosomally normal fetuses with increased nuchal translucency at 10-14 weeks' gestation. A total of 63 chromosomally normal fetuses with a first-trimester nuchal translucency thickness of 3 mm or more were evaluated. In ongoing pregnancies, follow-up scans were performed to detect or exclude additional structural anomalies in the fetus. Follow-up of the live-born children was by questionnaires sent to parents or reviews of medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 0 publications
5
46
0
7
Order By: Relevance
“…Most studies agree that the risk of chromosome abnormality increases with the thickness of NT [9,12,13]. Most authors have chosen a cut-off measurement of 3 mm [9,11,12,21]. However, Nadel et al [13] use a 4-mm cut-off value and report a much higher chromosome abnormality detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies agree that the risk of chromosome abnormality increases with the thickness of NT [9,12,13]. Most authors have chosen a cut-off measurement of 3 mm [9,11,12,21]. However, Nadel et al [13] use a 4-mm cut-off value and report a much higher chromosome abnormality detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…The second affected fetus in this family had an increased NT measurement of 5.6 mm at 11 weeks of gestation and hydrops. A third fetus [11] had an NT measurement of 9.6 mm and hydrothorax at 96 days of gestational age. …”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported on pregnancy outcomes associated with enlarged NT in cases of SMA [10,11,12,13,14,15,16,17], and thus, thickened NT has been considered a possible early ultrasound scan sign of SMA. Occasional clinical presentations of SMA in the third trimester of pregnancy are lack of movements and/or hydrothorax/hydrops.…”
Section: Introductionmentioning
confidence: 99%
“…Also it should be mentioned that in a normal karyotype fetus, the appearance of a thickened NT is also strongly associated with structural defects such as major cardiac malformation and rare genetic syndromes. It is proven that there is an association between increased NT and miscarriage and prenatal death and adverse pregnancy outcome 10 . Proposed pregnancy work up in fetuses with increased NT and normal karyotype includes anatomy scan, fetal echocardiography and in selected cases, infection screening and genetic testing.…”
Section: Introductionmentioning
confidence: 99%